1983
DOI: 10.1080/03610738308258441
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated testing upon comprehension of informed consent materials by elderly volunteers

Abstract: One hundred elderly adults (mean = 71.3 years of age, range = 59-88 years) in four WAIS vocabulary subgroups (less than 40, 40-49, 50-59, greater than or equal to 60) served in an evaluation of the effects of using multiple comprehension test trials to improve informed consent procedures. Participants in Group I were given a single comprehension test and feedback before signing consent documents, while those in Group II were provided with as many as three comprehension trials, if necessary. All participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…Of the five negative studies, two were inconclusive regarding the effect of simplified, more readable consent forms on patient understanding Taub et al 1987). Two other reports on corrected feedback (Taub and Baker 1983) and the addition of an oral discussion to written information (Tindall et al 1994) produced mixed results. The latter study demonstrated improvement from pre-to postconsent, but the oral discussion did not add significantly to this improvement.…”
Section: Consent For Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the five negative studies, two were inconclusive regarding the effect of simplified, more readable consent forms on patient understanding Taub et al 1987). Two other reports on corrected feedback (Taub and Baker 1983) and the addition of an oral discussion to written information (Tindall et al 1994) produced mixed results. The latter study demonstrated improvement from pre-to postconsent, but the oral discussion did not add significantly to this improvement.…”
Section: Consent For Researchmentioning
confidence: 99%
“…Eight reported a positive association (Bjorn et al 1999;Young et al 1990;Taub et al 1986;Taub et al 1987;Sorrell 1991;Neptune et al 1996;Aaronson et al 1996;Agre et al 1994). Two studies that evaluated patients' vocabulary levels (as measured by the vocabulary subtest of the Wechsler Adult Intelligence Scale [WAIS]) found that performance on immediate as well as delayed tests of understanding varied directly with vocabulary level (Taub and Baker 1983;Taub et al 1981).…”
Section: Predictors Of Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The differences in understanding due to education were often large, especially compared with the improvements produced by the various interventions. For example, Taub and Baker 13 documented that a feedback intervention increased average understanding scores by 29%, but there was a 95% difference between the least educated quartile of research participants and the most educated quartile. However, they also acknowledged that participants' recall of the information presented to them during the interview may not always reflect their actual understanding of such information.…”
Section: Discussionmentioning
confidence: 99%
“…Taub and colleagues conducted a number of studies comparing elderly and non-elderly adults in their ability to recall information contained in informed consent forms (see, e.g., Taub, 1980). These studies typically demonstrated poorer retention among the elderly participants, as well as associations between retention and levels of education and verbal abilities (Taub, 1979;Taub & Baker, 1983;Taub, Baker, & Sturr, 1986;Taub, Kline, & Baker, 1981). Other researchers have found improvements in retention of informed consent material when this information is presented in a simplified manner (e.g.…”
Section: Introductionmentioning
confidence: 98%